Innovation of Banana Blossom Herbal Tea in Enhancing Interleukin-1 and Interleukin-2 Levels as an Immunomodulatory Approach for Cancer Prevention - SUSILAWATI HARAHAP; Siska Futri Nasution (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Cancer remains one of the foremost causes of mortality worldwide, including in Indonesia. Its steadily increasing prevalence has positioned cancer as a critical global health challenge and a major focus of international public health initiatives. Pathologically, cancer is characterized by the uncontrolled and progressive proliferation of abnormal cells, ultimately impairing immune system function. Phytochemical profiling of the banana blossom has revealed the presence of bioactive compounds, including alkaloids, phenolic steroids such as β-sitosterol, saponins, as well as flavonoids such as quercetin, tannins, anthraquinones, and terpenoids. Flavonoids and phenolic compounds within the banana blossom demonstrate potential immunoenhancing properties, exhibit antioxidant activity against free radicals, and function as immunomodulatory agents with prospective applications in cancer prevention. Purpose: This study aimed to evaluate the immunomodulatory and anticancer potential of banana blossom extract through IL-1 and IL-2 regulation using male rats as experimental models, assessed through ELISA. Research method: An experimental design was employed, encompassing the preparation of the herbal tea, metabolite profiling, and measurement of IL-1 and IL-2 levels in serum isolated from the blood of rats administered the banana blossom herbal tea. Results: A significant increase in IL-1 and IL-2 levels was observed following treatment with banana blossom herbal tea and quercetin in both experimental groups compared with the negative control group. Administration of the extract at a dose of 400 mg/kg BW, as well as quercetin, demonstrated higher immunostimulatory activity compared with levamisole as the positive control. Conclusion: Banana blossom herbal tea exhibits immunomodulatory activity through an immunostimulatory mechanism and possesses potential for development as a therapeutic agent in cancer prevention.